The Great Disconnect: Quantifying the Mismatch between STEM Skill Supply and Labor Market Demand in Ethiopian Engineering Education - Belay Sitotaw Goshu (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
Ethiopia’s rapid industrialization and infrastructure development demand a competent engineering workforce. However, persistent mismatches between graduate competencies and employer expectations undermine employability and national development goals. This study aimed to quantify skills gaps in Ethiopian engineering education across civil, electrical, mechanical, and chemical disciplines, identify perceptual differences among stakeholders, examine institutional and pedagogical determinants, and compare outcomes between Institutes of Technology (IoTs) and conventional university structures. A cross-sectional mixed-methods survey collected Likert-scale ratings from 320 graduates, 180 employers, and 140 instructors across seven universities. Descriptive statistics, non-parametric tests (Kruskal-Wallis, Mann-Whitney U), gap analysis, and visualizations (bar plots, heatmaps, radar charts, and box plots) were employed to assess alignment, stakeholder perceptions, and institutional/pedagogical influences. This is among the first studies in Ethiopia to simultaneously compare graduate, employer, and instructor perceptions, quantify domain-specific gaps, and explicitly contrast IoT versus conventional institutional models in relation to pedagogical practices and skills outcomes. Significant gaps (1.1–1.7 points on a 5-point scale) were found, largest in technical skills, discipline-specific knowledge, and generic technical competencies. Employers rated readiness substantially higher than graduates and instructors, with statistically significant divergence in technical domains. IoTs exhibited consistently smaller gaps (average reduction 0.20–0.25 points), lower lecture dominance, modestly higher project/problem-based learning, and stronger (though still limited) industry practitioner integration compared to conventional structures. Systemic misalignment between engineering curricula and labor-market needs persists, driven by lecture-heavy pedagogy, weak industry linkage, and institutional design differences. IoTs demonstrate structural advantages in reducing skills deficits. Shift toward active, project-based pedagogies, integrate industry practitioners systematically, scale IoT-inspired models nationwide, and establish continuous employer feedback mechanisms to align engineering education with Ethiopia’s industrialization priorities.